Uprość wyrażenie.

*załącznik* ​


Uprość Wyrażeniezałącznik class=

Odpowiedź :

Hej!

a]

x(x - 2) + 2(x + x² - 5) =

= x² - 2x + 2x + 2x² - 10 =

= 3x² - 10

b]

a(a - b) - 2a(b - a) =

= a² - ab - 2ab + 2a² =

= 3a² - 3ab

c]

s(-t + 1) - t(s - w + t) =

= -st + s - st + tw - t² =

= -t² + tw - 2st + s

d]

-m(n - o) - 3o(-m + n) =

= -mn + mo + 3mo - 3no =

= 4mo - mn - 3no

e]

c(a + b - 2c) + 2b(-c - a) =

= ac + bc - 2c - 2bc - 2ab =

= -2ab - bc + ac - 2c

f]

x(y² - y) + y(-x² + x) =

= xy² - xy - x²y + xy =

= xy² - x²y

Pozdrawiam! - Jula

=